Comparison of regional anesthetic techniques for postoperative analgesia after adult cardiac surgery: bayesian network meta-analysis - Zhou, Ke; Li, Dongyu; Song, Guang (Frontiers in Cardiovascular Medicine, 2023)
Background: Patients usually suffer acute pain after cardiac surgery. Numerous regional anesthetic techniques have been used for those patients under general anesthesia. The most effective regional anesthetic technique was still unclear. Methods: Five databases were searched, including PubMed, MEDLINE, Embase, ClinicalTrials.gov, and Cochrane Library. The efficiency outcomes were pain scores, cumulative morphine consumption, and the need for rescue analgesia in this Bayesian analysis. Postoperative nausea, vomiting and pruritus were safety outcomes. Functional outcomes included the time to tracheal extubation, ICU stay, hospital stay, and mortality. Results: This meta-analysis included 65 randomized controlled trials involving 5013 patients. Eight regional anesthetic techniques were involved, including thoracic epidural analgesia (TEA), erector spinae plane block, and transversus thoracic muscle plane block. Compared to controls (who have not received regional anesthetic techniques), TEA reduced the pain scores at 6, 12, 24 and 48 h both at rest and cough, decreased the rate of need for rescue analgesia (OR = 0.10, 95% CI: 0.016–0.55), shortened the time to tracheal extubation (MD = -181.55, 95% CI: -243.05– -121.33) and the duration of hospital stay (MD = -0.73, 95% CI: -1.22– -0.24). Erector spinae plane block reduced the pain score 6 h at rest and the risk of pruritus, shortened the duration of ICU stay compared to controls. Transversus thoracic muscle plane block reduced the pain scores 6 and 12 h at rest compared to controls. The cumulative morphine consumption of each technique was similar at 24, 48 hours. Other outcomes were also similar among these regional anesthetic techniques. Conclusions: TEA seems the most effective regional postoperative anesthesia for patients after cardiac surgery by reducing the pain scores and decreasing the rate of need for rescue analgesia.